2015
DOI: 10.1182/blood-2014-09-594515
|View full text |Cite
|
Sign up to set email alerts
|

Increased risk of thrombosis in FcγRIIA 131RR patients with HIT due to defective control of platelet activation by plasma IgG2

Abstract: Key Points Normal IgG and IgG2 differentially inhibit HIT antibody-dependent platelet activation according to the FcγRIIA H131R polymorphism. This variable effect of IgG and IgG2 probably explains the higher risk of thrombosis in patients homozygous for the FcγRIIA 131R allele.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
96
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(103 citation statements)
references
References 37 publications
7
96
0
Order By: Relevance
“…PEA and SRA reactivities were completely inhibited in the presence of 100 U/mL UFH, confirming that platelet activation was mediated by HIT antibodies (data not shown). Previous work has shown that patients with arginine at amino acid position 131 in the activating IgG receptor on platelets, FcγRIIa, are more likely to experience more severe HIT (thrombosis) due to the inability of normal IgG 2 present in plasma to compete with HIT antibodies for binding to the receptor . Patients with histidine at aa131 in FcγRIIa, on the other hand, are competent to be bound by both normal IgG 2 and IgG 1 , leading to greater protection from HIT antibody‐mediated platelet activation.…”
Section: Case Presentation/resultsmentioning
confidence: 99%
“…PEA and SRA reactivities were completely inhibited in the presence of 100 U/mL UFH, confirming that platelet activation was mediated by HIT antibodies (data not shown). Previous work has shown that patients with arginine at amino acid position 131 in the activating IgG receptor on platelets, FcγRIIa, are more likely to experience more severe HIT (thrombosis) due to the inability of normal IgG 2 present in plasma to compete with HIT antibodies for binding to the receptor . Patients with histidine at aa131 in FcγRIIa, on the other hand, are competent to be bound by both normal IgG 2 and IgG 1 , leading to greater protection from HIT antibody‐mediated platelet activation.…”
Section: Case Presentation/resultsmentioning
confidence: 99%
“…All assays were performed on the same day with platelets from each of the unselected donors tested, and the data obtained confirmed that SRA is the most sensitive functional assay to detect platelet‐activating PF4‐specific antibodies. Indeed, the sensitivity of SRA to high, intermediate, and low concentrations of 5B9 was ≥95%, and SRA was also positive with 9 of the 10 samples from patients with “likely HIT.” The use of washed platelets is likely essential for explaining the excellent performance of SRA, because the removal of plasma abolishes any competition between HIT antibodies and donors' IgG for binding to platelet FcγRIIA receptors . This benefit of washing platelets probably explains why heparin‐induced activation assay (HIPA), performed with WP collected from four independent donors and under stirring in microtiter plates, is also considered a gold standard for HIT diagnosis .…”
Section: Discussionmentioning
confidence: 99%
“…Several European groups made major contributions to the pathogenesis of DITPs 229 and developed test systems and treatment recommendations. Access of physicians and patients to appropriate laboratory testing is well developed in some European countries (e.g.…”
Section: European Research Contributionsmentioning
confidence: 99%